Kategorisasi Tingkat Kemandirian Belajar Siswa Madrasah Aliyah - Wal, Zaen; aulia, fitri (Educatio, 2019)
The purpose of this study was to determine the level of student learning independence, based on high, low and high categorization. Data is obtained based on the results of filling in the independence questionnaire. Research uses a quantitative approach with survey methods. The data measurement tool uses a scale questionnaire. Based on aspects of independence. Participants in this study were 18th grade students of the Putra Rajak MA MA totaling 18 students. Based on the results of the analysis obtained a score of 25 which if included in the rank formula, then vulnerable 11.1> 25.7 is in the "low" category. Based on the analysis, it can be seen that the level of student learning independence is in the low level category, that is, from 18 participants who were sampled in the study, 85% (12 participants) were included in the low category. The high category is 15% (6 participants), while the low result is 0%.